2020
DOI: 10.1186/s12917-020-2239-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gga-miR-155 on cell proliferation, apoptosis and invasion of Marek’s disease virus (MDV) transformed cell line MSB1 by targeting RORA

Abstract: Background: Marek's disease (MD) is caused by the oncogenic Marek's disease virus (MDV), and is a highly contagious avian infection with a complex underlying pathology that involves lymphoproliferative neoplasm formation. MicroRNAs (miRNAs) act as oncogenes or tumor suppressors in most cancers. The gga-miR-155 is downregulated in the MDV-infected chicken tissues or lymphocyte lines, although its exact role in tumorigenesis remains unclear. The aim of this study was to analyze the effects of gga-miR-155 on the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…PPARD knockdown decreased the expression of 39 genes by less than or equal to 0.5-fold ( Table 2 ). Among these genes, LPAR3 , GAL3ST1 , PTPN11 , and RORA are involved in apoptosis [ 29 , 30 , 31 , 32 ]. We examined the effect of Cd on the expression of 15 of the above genes ( Figure 5 , data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…PPARD knockdown decreased the expression of 39 genes by less than or equal to 0.5-fold ( Table 2 ). Among these genes, LPAR3 , GAL3ST1 , PTPN11 , and RORA are involved in apoptosis [ 29 , 30 , 31 , 32 ]. We examined the effect of Cd on the expression of 15 of the above genes ( Figure 5 , data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Many viral genes in MDV genome have been identified that may involve in MD development, such as, meq [ 47 ], viral telomerase RNA (vTR) [ 48 ], viral interleukin-8 (vIL-8) [ 49 ], phosphoprotein 38 (pp38) [ 50 , 51 ], and MDV miRNAs [ 52 ]. For host genome, some genes involved in MD pathogenies were identified, including MHC [ 27 , 53 ], gga-miR-155 [ 54 ], gga-miR-26a and NEK6 [ 55 ], IGFBP7 and TNFRSF8 [ 39 ]. Several studies also illustrated the mechanism of susceptive or resistance from the epigenomic level [ 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs), as 19-22 nucleotide non-coding RNAs, involve in multiple important biological processes by binding partially complementary sequences of its target gene mRNA 3'-untanslated region (3'-UTR) and repressing target gene functions. Many studies have demonstrated that miRNAs play important roles in resisting kinds of disease in birds, like Marek's disease virus, avian in uenza virus, bursal disease virus and others virus infection [6][7][8]. Our previous studies have also highlighted the critical role of miRNAs during MG-HS (Mycoplasma gallisepticum-Huangshi) infection in lung tissue of chicken embryo, including miR-19a, miR-130b-3p, miR-451 ect [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 88%